The Effect of Disclosing the Offbalance Sheet Arrangement on Libyan Commercial Banks Decisions in Granting Credit - الحاسی, جمعة; المسماري , ايهاب (Dirasat in Economics and Business, 2015)
The study aims to identify the effect of disclosing the offbalance sheet arrangement on Libyan commercial banks decisions in granting credit. As firms conceal their debits by offbalance sheet funding as the case where the capital lease is treated as operating lease which result in disproportionate financial and the comparison of these statements would be meaningless and show the unreal financial position of the firm. However, commercial banks and other users of financial reports rely greatly on these financial reports to obtain information and related explanations, which contribute in making investing and credit decisions, and the quality of these decisions is closely related to the extent of their ability to interpret the informational content via extracting certain financial ratios to examine the firm ability of repayment. The study adopted the experimental research where the sample was divided into two groups, the expert group and the experimental group, this type of research is well known in social science. The study also provided a scientific evidence proof that the disclosure of financing arrangements off-balance sheet has no effect on credit decisions made by the Libyan commercial banks. This was established through rejecting the alternative hypothesis and accepting the null hypothesis. Libyan commercial banks are recommended to educate their personnel regarding what is financial statements contain about off-balance financing arrangement and related risks. This task can be achieved with the assistance of accounting departments in Libyan colleges and the accounting and banking training centers. Further studies are also needed in this area.